Sustainable Landscape Construction: Materials and Products — Brick - Gail Hansen (EDIS)
ENH1148, a 1-page fact sheet by Gail Hansen, highlights the environmental impact, design strategies, and construction techniques for using bricks in landscape construction. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.